Remaining in Foster Care After Age 18 and Youth Outcomes at the Transition to Adulthood: A Review. Issue 3 (July 2019) - Jones, Loring
Many foster youth do not exit care for a permanency option and remain in foster care until they age out or are emancipated. Research findings have described the alarming circumstances of these former foster children's adaptation to emerging adulthood. Public policy over the past three decades has sought various means of improving outcomes for these former foster youth. This review examines the legislative history leading up to extended care, the research on youth leaving foster care, youth preferences for extended care, the competition of extended care with permanency options, and the effects of extended foster care on transition-age youth. The benefits that can be had from such an extension are outlined.